Research on the Combination of Commercially Available Thickeners and Commercially Available Nursing Food - Universal Design Food: UDF (can be Crushed with Gums) (Global Journal of Medical Research, 2020)
In Japan, a super-aging society, there is much debate about how to provide safe home care in the future. To provide safe nursing care food, it is necessary to consider not only the nutritional aspect of the diet but also the dietary form. In the case of diminished or impaired swallowing function, it is useful that the viscosity of the diet matches the ability of the care recipient to swallow the food. Therefore, in this study, we report the viscosity measurement using a commercially available thickener and a commercially available universal design food (which can crush with gums) by changing the blending amount and combination of them. In this study, we used commercially available thickener A, and thickener B, which can purchase at pharmacies and three types of commercially available universal design foods (which can crush with gums) can purchase at pharmacies. In the case of foods having a large amounts of carbohydrates, the thickener B (high in thickening polysaccharides) can stabilize the viscosity and is suitable for adjusting the viscosity.
Keywords: thickener; nursing food; viscosity test